The Role of Principal Leadership in Improving Teacher Work Ethic at SDN Mancogeh - Ardiansyah Kurniawan; Heru Ramdani; Dede Aji Mardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Leadership is a person's ability to convince other people so that other people willingly work and are invited to carry out their wishes or ideas. The research aims to determine the work ethic of teachers at SDN Mancogeh and the leadership role of the principal in improving the work ethic of teachers at SDN Mancogeh. The research method used is qualitative by interpreting a phenomenological perspective, namely how a researcher is able to understand and appreciate the leadership of the school principal in improving the work ethic of teachers. This work ethic has experienced a decline as seen in several things which can be concluded, namely that there is no discipline towards teachers. Based on their teaching, teachers can master the material and various methods, have the motivation and freedom to develop their talents to support the learning process. Teachers are able to master the basics and principles of teaching according to the characteristics of students so that it is easier to choose the right learning method.